Frame structure analysis model for the effect of typical tunnel diseases on lining structure. Issue 4 (October 2021) - Koga, D R; Lin, Q W; Zhang, X S; Han, W; Jiang, Y J; Luan, H J
Abstract: The frame structure analysis method has been generally applied for the tunnel structure design, which was widely utilized due to its fast calculation speed and convenient modeling. In this paper, the frame analysis model was established to explore the effect of typical tunnel diseases of voids and lining insufficient thickness on the mechanical and deformation behavior of concrete linings. At first, the lining model with the diseases of void and lining insufficient thickness was established in the frame structure analysis platform. Subsequently, the lining inner force (taking the bending moment as an example) and the deformation behavior were explored. At final, the differences in the deformation behavior were investigated with different vertical loading conditions. The main results in this paper revealed that when the vertical loosening pressure can be transferred to the lining structure within the void zone, the maximum positive bending moment of the lining is located near the crown, while the maximum negative is at the shoulder, and the phenomenon of internal bending mainly occurs in the void area, and the phenomenon of external bending occurs at the shoulder. The lining has a significant downward displacement at the crown, while the deformation direction of the structure is outward at the shoulder. However, when the vertical loading cannot be transferred to the lining within the void zone, the obvious phenomenon of deformation outwards will occur within the void zone.